2018
DOI: 10.7754/clin.lab.2017.170925
|View full text |Cite
|
Sign up to set email alerts
|

The Activity of Alcohol Dehydrogenase Isoenzymes and Aldehyde Dehydrogenase in the Sera of Patients with Autoimmune Hepatitis

Abstract: The activity of total ADH and class I isoenzymes in the sera of patients with autoimmune hepatitis is increased, and it seems to be caused by the release of alcohol dehydrogenase from damaged liver cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…We have also observed that ADH I activity was elevated in the serum of patients with metastatic liver cancer (8). Furthermore, we have reported that the activity of class I alcohol dehydrogenase was significantly higher in the serum of patients with autoimmune hepatitis or nonalcoholic fatty liver disease than in healthy controls (24,25). In our study, we excluded women with different hepatobiliary diseases.…”
Section: Discussionmentioning
confidence: 83%
“…We have also observed that ADH I activity was elevated in the serum of patients with metastatic liver cancer (8). Furthermore, we have reported that the activity of class I alcohol dehydrogenase was significantly higher in the serum of patients with autoimmune hepatitis or nonalcoholic fatty liver disease than in healthy controls (24,25). In our study, we excluded women with different hepatobiliary diseases.…”
Section: Discussionmentioning
confidence: 83%
“…Numerous studies have demonstrated changes in the activity of alcohol dehydrogenase (ADH), its isoenzymes and aldehyde dehydrogenase (ALDH) in the blood serum of patients with various liver diseases, including hepatitis C, liver tumors, fatty liver disease, and AIH (Chrostek and Szmitkowski 2000 ; Jelski et al 2008 , 2017 , 2018a , 2018b ). These liver diseases showed statistically higher activity of class I ADH and total ADH in the serum of patients than in healthy subjects and the results suggest a potential clinical role for ADH (especially class I ADH) as marker for liver disorders.…”
Section: Introductionmentioning
confidence: 99%
“…In our previous investigations we have found that the activity of alcohol dehydrogenase (ADH) and aldehyde dehydrogenase (ALDH) were significantly higher in the serum of patients with different liver diseases (e.g. hepatitis C, autoimmune hepatitis, fatty liver disease) than in healthy subjects (Jelski et al, 2018a;Jelski et al, 2018b;Jelski et al, 2018c).…”
Section: Introductionmentioning
confidence: 99%